Current evidence for the diagnostic value of gadoxetic acid‐enhanced magnetic resonance imaging for liver metastasis. Issue 9 (16th February 2016) - Tsurusaki, Masakatsu; Sofue, Keitaro; Murakami, Takamichi
Abstract : A variety of imaging techniques, including ultrasonography (US), multidetector computed tomography (MDCT), magnetic resonance imaging (MRI) and positron emission tomography combined with CT scan (PET/CT), are available for diagnosis and treatment planning in liver metastasis. Contrast‐enhanced MDCT is a relatively non‐invasive, widely available and standardized method for hepatic work‐up. Gadoxetic acid (gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid; EOB Primovist®]) is a recently developed liver‐specific hepatobiliary MR contrast agent that offers both dynamic imaging as well as liver‐specific static hepatocyte imaging, referred to as the hepatobiliary phase. Following contrast injection, this technique reveals dynamic vascular phases (arterial, portal venous and delayed phases), in addition to the hepatobiliary phase upon uptake by functional hepatocytes. The overall sensitivity of gadoxetic acid‐enhanced MRI was significantly higher than that of contrast‐enhanced CT. Specifically, the higher sensitivity of gadoxetic acid‐enhanced MRI was observed in lesions smaller than 1 cm in diameter. Gadoxetic acid‐enhanced MRI is considered an extremely useful tool for the diagnosis of liver metastases. Future studies will focus on diagnostic algorithms involving combinations of modalities such as MRI, MDCT and/or 18 F‐fluorodeoxyglucose PET/CT, which may impact the treatment plan for these patients.